Law and Literature: A Still-thriving Relationship - Talavera, Pedro, (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
What kind of relationship exists between law and literature? Why have so many great jurists and philosophers used literature to explore their own disciplines? What were they looking for, and what did they find? What can law learn from literature, and how does literature reflect legal praxis? This book takes us on a fascinating journey through those questions and their answers. The first part offers a diachronic and thematic overview of the law and literature movement, showing how literature has influenced new ways of thinking about law from a narrative, hermeneutic, humanistic, ethical, and critical perspective. The second part analyzes the value of literature in the education of students, lawyers, and judges. And the third section presents a captivating analysis of the literary notion of justice and the relationship between literature and the economic analysis of law.